2017
DOI: 10.1681/asn.2016111210
|View full text |Cite
|
Sign up to set email alerts
|

ELABELA and an ELABELA Fragment Protect against AKI

Abstract: Renal ischemia-reperfusion (I/R) injury is the most common cause of AKI, which associates with high mortality and has no effective therapy. ELABELA (ELA) is a newly identified 32-residue hormone peptide highly expressed in adult kidney. To investigate whether ELA has protective effects on renal I/R injury, we administered the mature peptide (ELA32) or the 11-residue furin-cleaved fragment (ELA11) to hypoxia-reperfusion (H/R)-injured or adriamycin-treated renal tubular cells ELA32 and ELA11 significantly inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 115 publications
(155 citation statements)
references
References 51 publications
(85 reference statements)
11
143
0
1
Order By: Relevance
“…Slowly, the biological functions of ELA are starting to be revealed. Chen et al [13]. reported that ELA treatment markedly improves acute kidney injury in vitro and in vivo through inhibiting apoptosis, reducing inflammatory response, suppressing fibrosis and related markers (TGF-β1, fibronectin, vimentin, and collagen 1), and decreasing autophagy and the DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Slowly, the biological functions of ELA are starting to be revealed. Chen et al [13]. reported that ELA treatment markedly improves acute kidney injury in vitro and in vivo through inhibiting apoptosis, reducing inflammatory response, suppressing fibrosis and related markers (TGF-β1, fibronectin, vimentin, and collagen 1), and decreasing autophagy and the DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Sections and cells were detected by TUNEL assay using an In Situ Cell Death Detection Kit (Roche, Mannheim, Germany) as described previously (Chen et al . ). DHE staining (Beyotime, Shanghai, China), a marker for oxidative stress, was performed on renal cryosections.…”
Section: Methodsmentioning
confidence: 97%
“…For immunofluorescence staining, primary antibody against PDGFRα (AF1062, 1:200 dilution, R&D Systems) or Ki67 (sc15402, 1:100 dilution, Santa Cruz) was applied overnight. The sections were then incubated with anti‐goat or anti‐rabbit secondary antibody followed by DAPI staining, and images were taken . The number of cells with positive staining for both Ki67 and PDGFRα per field was determined.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were then incubated with anti-goat or anti-rabbit secondary antibody followed by DAPI staining, and images were taken. 20,21 The number of cells with positive staining for both Ki67 and PDGFRα per field was determined.…”
Section: Histological Immunohistochemical Staining and Immunofluomentioning
confidence: 99%